2020
DOI: 10.1016/j.prdoa.2020.100076
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to a strict medication protocol can reduce length of stay in hospitalized patients with Parkinson's Disease

Abstract: Background Patients with Parkinson's Disease (PD) are at higher risk of complications when admitted to the hospital. Delays in PD medications and use of contraindicated medications contribute to the increased risk and prolong their lengths of stay (LOS). Using a hospital-wide PD protocol, we aimed to ensure PD medications were placed with “custom” timing to resemble the home schedules, and also to avoid ordering or administering contraindicated medications. Material and methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…The HUMC team was able to successfully add the “Custom” option as a default frequency for selected PD medications for which timing is critical and eliminate the default frequency settings (non-custom) options from being available to choose ( Figure 2 ). With these changes, HUMC saw nearly a threefold increase in appropriate (custom) placement of PD medication orders ( Azmi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The HUMC team was able to successfully add the “Custom” option as a default frequency for selected PD medications for which timing is critical and eliminate the default frequency settings (non-custom) options from being available to choose ( Figure 2 ). With these changes, HUMC saw nearly a threefold increase in appropriate (custom) placement of PD medication orders ( Azmi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… 46 Another study on Parkinson's Disease stated that strict protocol adherence to the therapy could reduce LOS with a decrease in the actual/expected LOS ratio from 1.54 to 1.32 (p < 0.05). 47 The dosage form is one of the factors that affect compliance. Some studies suggested that compliance could be maintained significantly more effectively when using injectable antipsychotics compared to oral antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies stated that LOS was not statistically significantly reduced in patients receiving LAIAs following treatment with oral antipsychotics. 23 , 47 , 48 Meanwhile, another study showed that LOS was associated with patients discharged from hospital [aOR: 3.65 (1.66–8.01), p = 0.001] and treatment for antipsychotic extrapyramidal side effects during hospitalization [aOR: 3.45 (1.32–9.03), p = 0.012]. Patients who had more interactions with medical providers during psychotic episodes prior to presentation at the unit were less likely to have a long LOS [aOR: 0.35 (0.16–0.76), p = 0.008].…”
Section: Discussionmentioning
confidence: 99%
“…The patient's usual schedule of antiparkinsonian medications should be maintained peri-operatively if enteral intake is permitted. Adherence to the patient's home schedule, education of healthcare providers on the importance of medication timing and avoidance of contraindicated drugs have all been shown to shorten the duration of hospital stay [14]. This can be a challenge for patients with advanced disease requiring frequent dosing or for patients who cannot receive oral medication due to fasting or surgical considerations.…”
Section: The Medication Problems That Anaesthetists Face Withmentioning
confidence: 99%